2015
DOI: 10.1159/000439193
|View full text |Cite
|
Sign up to set email alerts
|

Peritoneal Dialysis in Asia

Abstract: Background: There is a growing demand of dialysis in Asia for end-stage renal failure patients. Diabetes mellitus is the leading cause of end-stage renal failure in many countries in Asia. Summary: The growth of peritoneal dialysis (PD) in Asia is significant and seeing a good trend. With the enhanced practices of PD, the quality of care in PD in Asia is also improved. Overall, PD and hemodialysis (HD) are comparable in clinical outcome. There is a global trend in the reduction of peritonitis rates and Asian c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 52 publications
(51 reference statements)
0
36
1
Order By: Relevance
“…An earlier study identified that PD accounted for >10% of all forms of renal replacement therapy worldwide in ESRD ( 26 ), however, this has reached 23% in Asia ( 27 ). During PD, the peritoneal mesothelium is usually exposed to hyperglycemic, hyperosmotic and acidic dialysis solutions, which may induce peritoneal fibrosis and eventual lead to PD failure.…”
Section: Discussionmentioning
confidence: 99%
“…An earlier study identified that PD accounted for >10% of all forms of renal replacement therapy worldwide in ESRD ( 26 ), however, this has reached 23% in Asia ( 27 ). During PD, the peritoneal mesothelium is usually exposed to hyperglycemic, hyperosmotic and acidic dialysis solutions, which may induce peritoneal fibrosis and eventual lead to PD failure.…”
Section: Discussionmentioning
confidence: 99%
“…This change is associated with the new bundled payment system, with its clear incentives for peritoneal dialysis [42]. Likewise, allowing reimbursement of PD, but not HD, has permitted to increase the use of PD over HD in many Asian countries like Hong Kong, Vietnam, Taiwan, Thailand, as well as in New Zealand and Australia over recent years [42,43]. The major reasons of under utilization of PD modality include (1) lack or inadequate pre-dialysis education [44] and patient's awareness of RRT options [7,44,45], and in particular the suitability and advantages of PD modality, (2) insufficient or lack of focus on patients' training and encouragement and support, especially for anxious and unwell patients who might be nervous about participating in their own treatment [46][47][48], (3) lack or inadequate training of nursing staff and nephrologists in PD therapy [45,49], (4) insufficient encouragement and support of medical and nursing staff to guide patients to chose or implement PD modality as a possible first choice therapy [45,50], (5) lack or insufficient appreciation of the concept of "integrated renal replacement therapy (RRT) program" [1], and (6) inadequate preparation or lack of a proper set up of an independent PD unit [51,52].…”
Section: Open Access Http://scidocorg/ijcdtphpmentioning
confidence: 99%
“…The annual growth rate of peritoneal dialysis was approximately 8%, exceeding that of hemodialysis (6-7%) [1]. The number of peritoneal dialysis patients in the Asia-Pacific region is significantly increasing each year [1,2]. This happened because peritoneal dialysis is more cost-effective than hemodialysis, which gives patients more freedom over their lives [1,3].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the governments allow reimbursement of peritoneal dialysis but not hemodialysis. Moreover, it is comparable in outcome and quality between two therapies [2]. The etiology of protein-energy wasting (PEW) in patients treated with either peritoneal or hemodialysis is comparable, and the prevalence of PEW is relatively high, ranging from 18% to 56% [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%